Building Continuous Integration Services for Machine Learning - Karlas, Bojan; Interlandi, Matteo; Renggli, Cedric; Wu, Wentao; Zhang, Ce; Babu, Deepak Mukunthu Iyappan; Edwards, Jordan; Lauren, Chris; Xu, Andy; Weimer, Markus (ACM SIGKDD International Conference on Knowledge Discovery and Data Mining (KDD 2020), 2020)
Continuous integration (CI) has been a de facto standard for building industrial-strength software. Yet, there is little attention towards applying CI to the development of machine learning (ML) applications until the very recent effort on the theoretical side. In this paper, we take a step forward to bring the theory into practice. We develop the first CI system for ML, to the best of our knowledge, that integrates seamlessly with existing ML development tools. We present its design and implementation details.